Social media and smoking behavior in college students - Augustina, Merrinda; Prabandari, Yayi Suryo; Bintoro, Bagas Suryo (Universitas Gadjah Mada, 2023)
Purpose: Indonesia is the largest cigarette consumer in Southeast Asia and has the third-highest number of smokers in the world. Smoking behavior in Indonesia causes 225,000 people to die each year. Social media exposure may have an impact on smoking behavior. Most students use social media and have a high probability of viewing information about cigarettes. Information from social media can affect smoking behavior in students. This study aims to investigate the relationship between social media use and smoking behavior among college students. Methods: This study employed a quantitative method with an observational design, involving 200 respondents. The instrument used in this study was a questionnaire designed to determine the relationship between social media use and smoking behavior among college students. The questionnaires were distributed using the checklist and short questions method, which was shared online via Google Form. Results: Most college students (80.5%) do not smoke, and most smokers (87.18%) are male. The bivariate analysis result shows that active response to pro-smoking messages has a significant relationship with smoking behavior (p<0,05). Conclusion: Pro-smoking messages in certain types of social media can influence smoking behavior in students.